Pedagogical practices and structural conditions of childhood education in rural settlements - Juliana Bezzon da Silva; Ana Paula Soares da Silva (Universidade Federal de Santa Catarina, 2019)
Children's education in rural areas is one of the main challenges in the construction of democratic Early childhood education in Brazil. Based on the premise that there is an interrelation between the structural conditions and the pedagogical practices of early childhood education, the issue was to discuss how these two aspects are evidenced and co-determined on a daily basis-day of two institutions of early childhood education of land reform settlements. It was analyzed the attendance in two preschools of rural settlements of the northeast of São Paulo's state, through participant observation and interviews with teachers, families, and children. It was verified that early childhood education in those areas is permeated by conditions and contradictions of the organization, the treatment given by the public management to each reality and the peculiar characteristics that configure them. It was concluded that pedagogical principles depend on a structure of work, which involves the organization of time, the existence of adequate spaces, enough, prepared and valued staff, to materialize and guide practices consistent with the specificities of the age group and the context of the life of children in the rural settlements.